Auditory Processing of Speech and Tones in Children With Tuberous Sclerosis Complex - O’Brien, Amanda M.; Bayet, Laurie; Riley, Katherine; Nelson, Charles A.; Sahin, Mustafa; Modi, Meera E. (Frontiers in Integrative Neuroscience, 2020)
Individuals with Tuberous Sclerosis Complex (TSC) have atypical white matter integrity and neural connectivity in the brain, including language pathways. To explore functional activity associated with auditory and language processing in individuals with TSC, we used electroencephalography (EEG) to examine basic auditory correlates of detection (P1, N2, N4) and discrimination (mismatch negativity, MMN) of speech and non-speech stimuli for children with TSC and age- and sex-matched typically developing (TD) children. Children with (TSC group) and without TSC (typically developing, TD group) participated in an auditory MMN paradigm containing two blocks of vowels (/a/ and /u/) and two blocks of tones (800 Hz and 400 Hz). Continuous EEG data were collected. Multivariate pattern analysis (MVPA) was used to explore functional specificity of neural auditory processing. Speech-specific P1, N2, and N4 waveform components of the auditory evoked potential (AEP) were compared, and the mismatch response was calculated for both speech and tones. MVPA showed that the TD group, but not the TSC group, demonstrated above-chance pairwise decoding between speech and tones. The AEP component analysis suggested that while the TD group has an increased P1 amplitude in response to vowels compared to tones, the TSC group does not show this enhanced response to vowels. Additionally, the TD group had a greater N2 amplitude in response to vowels, but not tones, compared to the TSC group. The TSC group also demonstrated a longer N4 latency to vowels compared to tones, which was not seen in the TD group. No group differences were observed in the MMN response. In this study we identified features of the auditory response to speech sounds, but not acoustically matched tones, which differentiate children with TSC from TD children.